2021
DOI: 10.3390/su132212719
|View full text |Cite
|
Sign up to set email alerts
|

Loyalty of Paratransit Users in the Era of Competition with Ride Sourcing

Abstract: As a mode serving urban mobility in developing countries, paratransit is experiencing competition with the fast and massive growth of ride sourcing. This study aims to investigate the loyalty of paratransit users in Bandung, Indonesia, in the era of competition with ride sourcing. Data collected by questionnaires and distributed to 400 paratransit users in Bandung were analysed using hierarchical structural equation modelling. The analysis shows that satisfaction is positively influenced by service quality var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 77 publications
0
6
0
Order By: Relevance
“…Chicago L, a rapid transit system, operates inside the city of Chicago. The number of L stations in the AM peak period has negative impact on TNC fare, highlighting possible competition between Chicago L and TNC ( 50 ). Interestingly, higher employment density at the origin is negatively associated with TNC fare, possibly reflecting the presence of infrastructure for non-motorized modes and improved land use ( 51 , 52 ).…”
Section: Model Estimation Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Chicago L, a rapid transit system, operates inside the city of Chicago. The number of L stations in the AM peak period has negative impact on TNC fare, highlighting possible competition between Chicago L and TNC ( 50 ). Interestingly, higher employment density at the origin is negatively associated with TNC fare, possibly reflecting the presence of infrastructure for non-motorized modes and improved land use ( 51 , 52 ).…”
Section: Model Estimation Resultsmentioning
confidence: 99%
“…From this broad set of alternatives, destination choice models are developed employing a random sample of 30 alternatives (inclusive of the chosen alternative). A similar random sampling process has been adopted in earlier literature for destination choice models (see Joewono et al, Ryan and Frank, Seong et al, and Dey et al for details) ( 5053 ).…”
Section: Data Preparationmentioning
confidence: 99%
“…Moreover, from other authors' research on the loyalty of paratransit users, it can be concluded that loyalty is positively influenced by satisfaction [38]. Satisfaction with paratransit's image and unique attributes sustains passengers' future loyalty intentions, depending on passengers' current personal characteristics (i.e., age, income, occupation) and trip characteristics (e.g., fare, vehicle ownership).…”
Section: Lee At Al [14]mentioning
confidence: 93%
“…Public transit users showed more interest in cycling than private vehicle users and, motorbike users were least interested in considering cycling as a transportation mode (43%), confirming that "NMT promotion can be tricky in a context with motorbikes and Paratransit in practice." [38]…”
Section: Interest In Bicycle Use As a Transportation Modementioning
confidence: 99%